Novella "The Earthquake in Chile" by Heinrich von Kleist in Serbian Translations - Pasula, Milica B. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Heinrich von Kleist is one of the most well-known names of the 19th-century German literature, an author of dramatic works and novellas which are still widely received on the world’s literary and theatrical stages. His novella, The Earthquake in Chile, stands out in а row of controversial literary works which had shocked his contemporaries and was met with waves of disapprovals and censorships. Kleist’s story has been translated into Serbian five times. It represents a linguistic as well as semantic challenge, not only in the original, but also in the translated interpretations. This paper focuses on the two versions of the translation by Raško Dimitrijević (1950/1978), as well as the translations of Marija Kon (1959), Zoran Gluščević (1964), and Jovica Aćin (2015). The main characteristics of the translational styles are analyzed, which include language interferences with German, stylistic features, transcription of personal names and toponyms, and obscurities in the translated texts. The analysis shows that the complexity of the original influenced many translational solutions, but also enabled an insight into various translational techniques and strategies. The aim of this paper is to specify the differences and peculiarities of the translations, to determine the main aspects of the translational poetics, and to highlight the crucial interpretative challenges of the original text.
Keywords: literary translation; translational poetics; German literature; Raško Dimitrijević; Marija Kon; Zoran Gluščević; Jovica Aćin